2011
DOI: 10.1080/09585192.2011.584404
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived support in employee development affect personnel turnover?

Abstract: This paper focuses on the question whether it is beneficial for firms to invest in the general skills of their workforce or that these training investments merely encourage personnel turnover. We examine two contrary theoretical perspectives on how investments in employee development are related to their turnover behaviour. Estimation results derived from a sample of 2,833 Dutch pharmacy assistants show that participation in general training does not induce the intention of assistants to quit, as predicted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 39 publications
(65 reference statements)
6
69
0
Order By: Relevance
“…This study also confirms the work by Koster et al (2009);De Moura et al (2008); Boselie and Wiele (2001); Bowen and Ostroff (2000); Clark et al (1998);and Freeman (1978) that demonstrates a negative relationship between job satisfaction and turnover intentio n: A highly satisfied employee will have a lower tendency to leave the organization, and conversely a highly dissatisfied employee is more likely to leave the organization and change employer. Furthermore, the findings of this research are partly in line with the results by Chen and Wang (2014) whose study showed a partially mediated relationship between the HR attribution of commitment focus towards turnover intention, and a fully mediated relationship between the HR attribution of control focus toward s turnover intention.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This study also confirms the work by Koster et al (2009);De Moura et al (2008); Boselie and Wiele (2001); Bowen and Ostroff (2000); Clark et al (1998);and Freeman (1978) that demonstrates a negative relationship between job satisfaction and turnover intentio n: A highly satisfied employee will have a lower tendency to leave the organization, and conversely a highly dissatisfied employee is more likely to leave the organization and change employer. Furthermore, the findings of this research are partly in line with the results by Chen and Wang (2014) whose study showed a partially mediated relationship between the HR attribution of commitment focus towards turnover intention, and a fully mediated relationship between the HR attribution of control focus toward s turnover intention.…”
Section: Resultssupporting
confidence: 78%
“…According to Bowen and Ostroff (2000) and Koster et al (2009), job satisfaction is one of the most researched work-related variables, and has a significant relationship with turnover intentions. An obvious reaction to dissatisfaction is to leave the company and change employers (Clark et al 1998;De Moura et al 2008;Mahdi et al 2012), and conversely, employees who have high satisfaction levels are more motivated to stay within the company.…”
Section: Job Satisfaction As a Mediator Between Hr Attributions And Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies have recommended that providing training opportunities to employees will lead to higher level of job satisfaction (Pare & Tremblay, 2007;Georgellis & Lange, 2007, Edgar & Geare, 2005. A study conducted in the Dutch pharmacy assistants found a negative relationship between training and employees" turnover intentions mediated by job satisfaction (Koster, Grip & Fouarge, 2009). Similarly, Cheng and Waldenberger (2013) conducted a study to examine the relationship between training expectations and turnover intentions mediated by job satisfaction among Chinese employees.…”
Section: Job Satisfaction As a Mediating Variablementioning
confidence: 99%
“…Thus, personal development can be seen as a way in which the employer and employee can participate in social exchanges because the employer is giving the employee opportunities to acquire and develop valuable resources in the form of skills, abilities and knowledge (Koster, de Grip, & Fouarge, 2011). The theory of social exchange (Blau, 1964) posits that an employee and their employer participate in an ongoing exchange of resources that occurs within a framework of rules and norms of reciprocity, such that when an employee receives resources from the other party they will feel obliged to repay in kind.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%